Tanggung Jawab Notaris Terhadap Penyalahgunaan Keadaan Dalam Kontrak Baku Perjanjian Kredit Bank - Sandra Aprilian (Program Studi Kenotariatan Program Magister Fakultas Hukum UNTAG Semarang, 2024)
Notaries should be responsible for drafting and issuing credit agreements between banks and debtors in order to provide legal certainty for all parties involved. In an effort to achieve legal certainty, especially in banking credit agreements with standard clauses, Notaries must ensure that their duties are carried out in accordance with applicable principles and provisions. This research aims to analyze unbalanced standard clauses in credit agreements made by Notaries and to examine the liability of Notaries for credit agreements that utilize standard clauses. The approach method used is the doctrinal legal research method, using literature examination or secondary data to examine relevant regulations and literature. The preparation of this research uses an analytical descriptive approach which aims to explain the data or describe the object of the problem being studied. The results of the research show that the responsibility of the Notary for credit agreements that apply standard clauses is that if the agreement made by the Notary has elements of unlawful acts, the Notary has an obligation to be responsible in accordance with civil provisions by providing compensation to parties who lose as a result of the agreement in accordance with the provisions stipulated in Article 84 of Law Number 2 of 2014 concerning Notary Offices.